NURSING CARE FOR THE HEALTH OF INDIGENOUS POPULATIONS: SCOPING REVIEW - Monteiro, Marcelo Anderson Cavalcante; Siqueira, Luana Eugênia de Andrade; Frota, Natasha Marques; Barros, Lívia Moreira; Holanda, Violeta Maria de Siqueira (Cogitare Enfermagem, 2023)
Objective: to identify in the literature the nursing care actions for the health of indigenous populations. Method: this is a scoping review, whose search was conducted in September 2022 in the following databases: Nursing Database (BDENF), CAPES Theses and Dissertations Catalog, Google Scholar, Latin American and Caribbean Literature on Health Sciences (LILACS), Pan American Health Organization (PAHO), National Library of Medicine and National Institutes of Health (PUBMED) and Scientific Electronic Library Online (SCIELO). The results were evaluated by summarizing the selected articles. Results: the main actions directed to the indigenous population were nursing consultations and health promotion and prevention activities. The main difficulty encountered in relation to indigenous peoples is the language barrier. Conclusion: the nursing team encounters difficulties, such as: the difficult location of the villages; high work overload due to the lack of medical professionals; language barrier; and inadequate conditions.